Small Modular Reactor Human-System Interface and Control Room Layout Design. (November 2019) - LaFerriere, Kevin; Stevens, Jessica; NuScale, Ryan Flamand
The NuScale Small Modular Reactor (SMR) is premised on well-established nuclear technology principles with a focus on integration of components, simplification or elimination of systems, automation, and use of passive safety features. Traditional nuclear power plants have in some cases operated up to four modules from a single control room. Due to the unique nontraditional operating characteristics of this technology a state-of-the art control room design was needed to ensure proper staffing totals for monitoring and control of multiple modules (twelve) from a single control room. To accomplish this, the human system interface and control room layout must translate the functional and task requirements needed for safe operation of the plant into the detailed design of workstations, alarms, controls, navigation, and other needs of the control room operations staff.